Investigating the Effective Psychological and Economic Factors in Choosing Machine-woven Carpets from the Viewpoints of the Citizens of Ahwaz, Iran - Sadeghi, Minoo (Advances in Social Sciences Research Journal, 2019)
Carpet is generally one of the basic necessities of Iranian families and from a long time ago the use of this product is considered as one of the requirements of Iranian life. According to this necessity, the purpose of this study is to investigate and identify the most effective economic and psychological factors in the choice of machine-woven carpet. The present study is an applied study with a descriptive-analytical approach. Its statistical population includes Ahwazi citizens of Iran visiting all the branches of Imam Reza Carpet Market during the winter of 2017 in order to select or buy carpets. From among these people, 270 were randomly selected and surveyed. The data gathering instrument was a researcher-made questionnaire. In order to analyze the data in this study, the exploratory factor analysis, confirmatory factor analysis, Pearson correlation coefficient., independent-samples t-test, one-way ANOVA test and Duncan's test were used. The results of this research indicated that regarding the viewpoints of Ahwazi citizens visiting Imam Reza Carpet Market, both economic and psychological factors were effective in choosing machine-woven carpets, however, the economic and price-related factors had the highest effect.